2012
DOI: 10.1021/jp210853h
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Fate of Methacrolein. 2. Formation of Lactone and Implications for Organic Aerosol Production

Abstract: We investigate the oxidation of methacryloylperoxy nitrate (MPAN) and methacrylicperoxy acid (MPAA) by the hydroxyl radical (OH) theoretically, using both density functional theory [B3LYP] and explicitly correlated coupled cluster theory [CCSD(T)-F12]. These two compounds are produced following the abstraction of a hydrogen atom from methacrolein (MACR) by the OH radical. We use a RRKM master equation analysis to estimate that the oxidation of MPAN leads to formation of hydroxymethyl−methyl-α-lactone (HMML) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 46 publications
4
78
0
Order By: Relevance
“…This translates to a calculated 0% yield of HMML in the HMPPN + OH reaction (100% reacts with O 2 ). In comparison, Kjaergaard et al 17 estimated the decomposition of A* to HMML is fast under the conditions they studied (k (A*-HMML) B 4 Â 10 9 s À1 ), translating to a 61-74% HMML yield from MPAN (2% is stabilized to A). The theoretical-derived kinetic results are consistent with observations for these C 4 APN-derived alkyl radicals.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This translates to a calculated 0% yield of HMML in the HMPPN + OH reaction (100% reacts with O 2 ). In comparison, Kjaergaard et al 17 estimated the decomposition of A* to HMML is fast under the conditions they studied (k (A*-HMML) B 4 Â 10 9 s À1 ), translating to a 61-74% HMML yield from MPAN (2% is stabilized to A). The theoretical-derived kinetic results are consistent with observations for these C 4 APN-derived alkyl radicals.…”
Section: Resultsmentioning
confidence: 95%
“…2 shows three possible pathways leading to SOA production that have been proposed by independent works. 13,17,18 The initial step of the MPAN photooxidation is OH addition to the double bond, primarily generating the energetically hot tertiary alkyl radical of MPAN (A*, Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…MACR can be oxidized to produce peroxymethacrylic nitric anhydride (MPAN), which is a precursor to methacrylic acid epoxide (MAE) and hydroxymethylmethyl-α-lactone (HMML), and these compounds can undergo reactive uptake to produce PM (Kjaergaard et al, 2012;Lin et al, 2013;Worton et al, 2013;Nguyen et al, 2015). Glyoxal produced from isoprene oxidation can contribute to PM production (Volkamer et al, 2007;Ervens and Volkamer, 2010;McNeill et al, 2012;Marais et al, 2016).…”
Section: Molecular Tracersmentioning
confidence: 99%
“…These uncertainties stem from, for example, the large range in reported yields for isoprene nitrates (4-15 %) (Paulot et al, 2009a), disagreements up to 90 % in reported MAC and MVK yields from the low-NO pathway (Liu et al, 2013, and references therein), various proposed sources of SOA from the high-NO pathway Kjaergaard et al, 2012;Lin et al, 2013), missing contributions to SOA mass from the low-NO pathway , uncharacterized fates of oxidized species like HPALDs (which may have isomer dependence), incomplete understanding of oxygen incorporation (Peeters et al, 2009;Crounse et al, 2013), and under-characterized impact of RO 2 lifetimes on chamber results . The OH oxidation of α-pinene (Eddingsaas et al, 2012) and other monoterpenes is less well characterized than that of isoprene, but, in general, proceeds through analogous steps.…”
Section: Oh Oxidationmentioning
confidence: 99%
“…19,24,26,and 30): experiments aimed specifically at studying chemistry leading to SOA formation have overlapping goals with those described above. One focus was the evaluation of the SOA-formation route from APNs by the proposed dioxo ketone, lactone, and epoxide mechanisms Kjaergaard et al, 2012;Lin et al, 2013), none of which has yet been validated by independent studies. However, the proposed epoxide chemistry has been integrated into some studies published soon after the proposal by Lin et al (2013) (Worton et al, 2013;Pye et al, 2013).…”
Section: Experimental Designmentioning
confidence: 99%